Posterior membranous tracheal injury during mckeown oesophagectomy. A case report with literature review - Gill, Theeran Kaur; Loo, Guo Hou; Muthkumaran, Guhan; Kosai, Nik Ritza (Frontiers in Oncology, 2025)
Minimally invasive techniques such as thoracoscopic or robotic surgical approaches for oesophageal pathologies have been gaining traction as the preferred method of surgical technique. McKeown’s minimally invasive oesophagectomy has been shown to reduce hospitalisation, with reduced cardiopulmonary morbidities. However, it is not without complications, and an iatrogenic tracheobronchial injury (TBI) could occur intraoperatively during anatomical plane dissection. We report a case of iatrogenic posterior membranous tracheal injury during the thoracic dissection of a McKeown’s oesophagectomy, detected intraoperatively and patient recovered without any complications. The diagnosis of TBI involves a multicentric approach. Confirmation of the diagnosis and classification of TBI based on clinical signs, radiological studies, and endoscopy procedures such as bronchoscopy are necessary to tailor the best possible management for the patient. In cases where a full-thickness airway defect exceeds 2 cm and is detected intraoperatively, immediate primary repair is advised to optimize outcomes. TBI pose significant clinical challenges, particularly in cases of iatrogenic injury during procedures such as minimally invasive oesophagectomy. While the overall incidence of TBI remains low, awareness of risk factors and vigilant monitoring during procedures is paramount. While TBI remains rare, its management shares principles with oncological oesophageal surgery, making this case pertinent to surgical oncology practice. The evolving landscape of diagnostic techniques, including bronchoscopy and advanced imaging modalities, facilitates prompt and accurate identification of injuries, enabling timely intervention.